Wiley StatsRef: Statistics Reference Online 2019
DOI: 10.1002/9781118445112.stat07883
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Social Contact Surveys Relevant for the Spread of Infectious Diseases

Abstract: To understand how infections spread through a population, it is crucial to have a correct description of the transmission network. However, it is often impossible to observe transmission of infection directly. To compensate for this lack of direct observations on the structure of the transmission network, we can use information on the social contact network obtained from sociological surveys asking people how frequently they experience at risk events for transmission. We focus on those studies that collect dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…We computed R 0 as the leading eigenvalue of the next generation matrix informed by the contact matrix while assuming the transmission rates to be pro-portional to the social contact rates, i.e. “the social contact hypothesis” [13, 14] from the 2010 survey and from the eight waves of the CoMix survey separately. To account for sampling variability, we generated 10,000 contact matrices via bootstrapping using the SocialMixr package [15].…”
Section: Discussionmentioning
confidence: 99%
“…We computed R 0 as the leading eigenvalue of the next generation matrix informed by the contact matrix while assuming the transmission rates to be pro-portional to the social contact rates, i.e. “the social contact hypothesis” [13, 14] from the 2010 survey and from the eight waves of the CoMix survey separately. To account for sampling variability, we generated 10,000 contact matrices via bootstrapping using the SocialMixr package [15].…”
Section: Discussionmentioning
confidence: 99%
“…We computed as the leading eigenvalue of the next generation matrix informed by the contact matrix while assuming the transmission rates to be proportional to the social contact rates, i.e. “the social contact hypothesis” 15 , 26 from the 2010 survey and from the eight waves of the CoMix survey separately. To account for sampling variability, we generated 10,000 contact matrices via bootstrapping using the SocialMixr package 27 .…”
Section: Methodsmentioning
confidence: 99%
“…The next generation matrix approach was used to estimate changes in the reproduction number (R t ) (9). The reproduction number was estimated by multiplying R 0 prior to physical distancing interventions by the ratio of the dominant eigenvalues of the POLYMOD UK (6) and observed contact matrices under the assumptions of the social contact theory that the transmission rate is proportional to rate of social contacts (5,19). A meta-analysis reported that, prior to interventions, R 0 followed a normal distribution with a mean of 2.6 and standard deviation of 0.54 (11).…”
Section: Methodsmentioning
confidence: 99%
“…In March, 2020, as transmission of SARS-CoV-2, the virus that causes Coronavirus Disease 2019 (COVID- 19), was increasing across Canada, provincial and local governments implemented a variety of nonpharmaceutical public health measures (1). As a main route of transmission of SARS-CoV-2 is close contact with an infected individual (2), these restrictions were implemented to reduce contact between individuals and included a variety of physical distancing measures (1).…”
Section: Introductionmentioning
confidence: 99%